2022
DOI: 10.1177/15394492221090624
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Japanese Version of the Engagement in Meaningful Activities Survey

Abstract: Objectives: To create a Japanese version of the Engagement in Meaningful Activities Survey (EMAS) and assess internal consistency, test–retest reliability, convergent and structural validity. Method: We conducted a cultural translation and validation study of the Japanese version of the EMAS (EMAS-J) in a sample of 96 community-dwelling older adults in the Tohoku Region of Japan. Results: Internal consistency of the EMAS-J (α = .91) was very good. Low to moderate correlations were found with indicators of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A second component related to social environment as a motivating factor to perform and engage in activities (SC)—comprised of items 6 and 7. The two-factor structure in the EMAS has been confirmed in the original EMAS (Eakman et al, 2010a) and the translated Korean, Spanish, Polish and Japanese versions (Bożek and Tokarz, 2017; Kawakatsu et al, 2022; Nam et al, 2018; Prat et al, 2019). However, the CFA showed a poor fit of the model of Eakman et al (2010a) (SEC and PCC) in our sample of adults and demonstrated an improved model fit of the Flemish model.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…A second component related to social environment as a motivating factor to perform and engage in activities (SC)—comprised of items 6 and 7. The two-factor structure in the EMAS has been confirmed in the original EMAS (Eakman et al, 2010a) and the translated Korean, Spanish, Polish and Japanese versions (Bożek and Tokarz, 2017; Kawakatsu et al, 2022; Nam et al, 2018; Prat et al, 2019). However, the CFA showed a poor fit of the model of Eakman et al (2010a) (SEC and PCC) in our sample of adults and demonstrated an improved model fit of the Flemish model.…”
Section: Discussionmentioning
confidence: 71%
“…The EMAS-VL also moderately correlated with the GHQ-12 which assesses mental health. Health-related measures have already been used to measure construct validity in translated EMAS versions such as the 36-Item Short-Form Health Survey (SF-36; Kawakatsu et al, 2022; Cheraghifard et al, 2022), Psychological Meaningfulness Scale (Bożek and Tokarz, 2017), or Center for Epidemiologic Studies Depression Scale (Cheraghifard et al, 2022). They all showed a moderate positive correlation with the EMAS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations